The State of Art about drainage basins and its relationship with Environmental Education (Research, Society and Development, 2020)
This work is a partial result of greater research which objective was to analyze the academic production on the subject of Drainage Basins and Environmental Education carried out from 2010 to 2018, in the editions of the National Meeting of Researchers in Science Education ( ENPEC), the Electronic Journal of the Master in Environmental Education (REMEA), and the Digital Library of Theses and Dissertations (BDTD). The methodology is based on bibliographic research called the State of the Art. 23 works available on databases were used. They were downloaded and read in full to be applied to this research. The results show that Drainage Basins and Environmental Education are worked in different regions and contexts in very incipient, decontextualized, and fragmented means. It is noticed that subjects need to be developed in a permanent and contextualized methods in school environments and higher education institutions, and as demand for public policies.